Green Tea Level on Growth Performance and Meat Quality in Finishing Pigs - Sarker, M.S.K.; Yim, K.J.; Ko, S.Y.; Uuganbayar, D.; Kim, G.M.; Bae, I.H.; Oh, J.I.; Yee, S.T.; Yang, C.J. (Pakistan Journal of Nutrition, 2009)
This study was designed to determinate the effects of green tea on growth performance and meat quality of finishing pigs. Ninety crossbreed "Landrace x Large White" pigs were assigned to 5 treatments a completely randomized design. The five dietary treatments were control (no green tea), antibiotic (30 ppm chlortetracycline) and 0.5, 1.0 and 2.0% of green tea added. The weight gain of pigs fed diets containing 2.0% green tea supplementation was significantly lower than that of the antibiotic supplemented (p<0.05). However, the feed intake and feed conversion ratio did not differ among treatments by dietary green tea addition (p>0.05). Crude protein in the carcass of pig showed significantly highest value in 1.0% green tea than control and other green levels (p<0.05) but similar value with antibiotic. The carcass grade was significantly increased in 0.5 and 1.0% green tea treatments (p<0.05) while Thiobarbituric Acid (TBA) value of pork was significantly decreased by 2.0% green tea supplementation (p<0.05).